Channeling efficiency reduction in high dose neutron irradiated silicon crystals for high energy and high intensity beam collimation and extraction. (4th August 2021) - Scandale, W.; D'Andrea, M.; Esposito, L.S.; Garattini, M.; Guillermain, E.; Mirarchi, D.; Montesano, S.; Natochii, A.; Rossi, R.; I. Smirnov, G.; Zhovkovska, V.; Murtas, F.; et al.
Abstract: The channeling process in bent silicon crystals are used since '70s to manipulate beams of high energy particles. During the last decade, several studies and experiments carried out by the UA9 Collaboration at CERN demonstrated the possibility to use bent crystals for beam collimation, extraction, focusing and splitting in particle accelerators. These crystals are subject to deterioration due to the interaction of the particles with the crystal lattice, degrading the beam steering performance. For this reason, robustness tests are crucial to estimate their reliability and operational lifetime. A ∼8% of reduction in channeling efficiency on crystals irradiated with 2.5·10 21 /cm 2 thermal neutrons was measured and reported in this manuscript. Extrapolations to possible operational scenarios in high energy accelerators are also discussed.